Application of Extreme Learning Machine in Predicting Short- Term Wind Speed - Chen C.P.; Tiong S.K.; Koh S.P.; Nasser A.A.; Abbas D.; Chooi F.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric load dispatching; Electric power transmission networks; Forecasting; Knowledge acquisition; Machine learning; Mean square error; Speed; Wind power; Developed model; Economic advantages; Extreme learning machine; Prediction accuracy; Root mean square errors; Scientific basis; Strong stability; Sustainable resources; Wind